Nitrogen conversion during the homogeneous and heterogeneous stages of sludge steam gasification: Synergistic effects of Fenton's reagent and CaO conditioner. (1st April 2019) - Lu, Geng; Liu, Huan; Zhang, Qiang; Wang, Jiaxing; Yi, Linlin; Hu, Hongyun; Yao, Hong
Graphical abstract: Highlights: Composite conditioners can reduce NH3 and HCN generation at each stage. The synergy on NOx precursors reduction in homogeneous stage accounted for 50.59–98.76% of final decrement. Nitrile-N and pyrrole-N in char converted to indole-N in tar with iron-catalyzing in heterogeneous process. Both char-N and tar-N can be decomposed to N2 in the existence of CaO. Abstract: Fenton's reagent (Fe 2+  + H2 O2 ) and CaO are the conditioners during sludge dewatering, which also showed abilities in NOx precursors control during drying and pyrolysis process that we have found before. This study further refined the effects of conditioners on homogeneous and heterogeneous processes during sludge steam gasification using a self-designed decoupling reactor. The results show that compared with raw sludge, the NH3 and HCN yields of conditioned sludge decreased by 13.71–17.67 mL/g and 17.77–23.45 mL/g at 873–1073 K respectively. 50.59–98.76% of decrement attributed to the synergistic effect of conditioners on volatiles homogeneous reforming, owing to the less NH3, HCN and tar-N yields in devolatilization product as well as the indirect enhancement of HCN hydrolysis. Fenton's reagent added alone exhibited a significant effect on volatiles heterogeneous reforming. During the interaction between volatiles and char, iron salts could catalyze the nitrile-N and pyrrole-N in char conversion to stable indoles in tar and inhibited the hydrolysis of amine-N to release NH3 . Calcium salts also showed a certain capability on the co-decomposition of quaternary-N in char and indoles/quinolones in tar to harmless N2 . Thus, the combination of Fenton's reagent and CaO can complementarily reduce the emission of NOx precursors at each stage of gasification.